Phenolic composition of monovarietal red wines regarding volatile phenols and its precursors - Lima, Adriana (2018)
The aim of this study was to characterise and compare wines from different grape varieties focusing on the volatile phenols and on the respective precursor compounds, both on the free form (p-coumaric, ferulic and caffeic acids) and as tartaric esters of hydroxycinnamic acids (caftaric, coutaric and fertaric acids). Fifty-eight commercial monovarietal red wines from eight selected grape varieties were used: Cabernet Sauvignon, Syrah, Aragonez, Castelão, Touriga Franca, Touriga Nacional, Trincadeira and Vinhão (Sousão). It was found that volatile phenol precursors exist mostly as esters of tartaric acid, with caftaric acid as the most abundant cinnamate (17–111 mg/L), followed by coutaric and fertaric acids. The predominant hydroxycinnamic acid was p-coumaric acid, the highest concentrations being found in Syrah and Touriga Franca (6–7 mg/L) and the lowest in Touriga Nacional and Trincadeira (2–3 mg/L). Touriga Nacional exhibits the highest difference between bound and free forms. Malvidin-3-O-(6-p-coumaroyl)-glucoside, a potential source of p-coumaric acid, was found in most of the wines with average values varying between 1 and 5 mg/L. Twenty-two percent of the wines analysed presented levels of volatile phenols above the perception threshold. Ethylphenols were the highest in Vinhão and Trincadeira, showing an average value well above the perception threshold. The concentrations found in Cabernet Sauvignon and Syrah wines were around ten times lower than those reported in previous works. The results show relevant differences among grape varieties but the availability of the precursors in meaningful amounts may not be the only factor explaining the formation of volatile phenols in wines.